The synthesis of TiC dispersed strengthened Mo alloy by freeze-drying technology and subsequent low temperature sintering. (June 2021) - Hu, Weiqiang; Du, Zunfeng; Dong, Zhizhong; Yu, Liming; Ahamad, Tansir; Ma, Zongqing
Abstract: The TiC dispersed strengthened Mo alloys were synthesized by novel freeze-drying technology and subsequent low-temperature sintering. With the introduction of TiC nanoparticles using freeze-drying technology, the sintered Mo-TiC alloys possess ultrafine grain size (2.38 μm), high density (99.3%) and high hardness (402±29 HV0.2 ). The agglomeration and growth of second phase particles in Mo-TiC alloys were effectively depressed by freeze-drying technology. Moreover, a theory about purification and strengthening is proposed. C-deficient TiC (Ti8 C5 ) will adsorb nearby oxygen impurities and even form TiO2 to purify Mo matrix. Furthermore, TiC (002), Ti8 C5 (0-24) and TiO2 (111) can form coherent interfaces with Mo (110) to strengthen their phase boundary and improve material strength. The stable phase interface can pin and limit the growth of these second phase particles, thus maintaining their small size (<50 nm). Graphical abstract: Image, graphical abstract